Philippine corporate governance environment and policy and their impact on performance and finance - Saldaña, Cesar G. (The Philippine Review of Business and Economics, 2000)
The Asian Development Bank initiated a study of Corporate Governance and Finance in Selected developing Member Countries in November 1998. The objectives of the study for the Philippines are to evaluate the history and current state of corporate governance in the Philippines; establish a sound analytic basis for policy and regulatory reform measures to strengthen corporate governance of Philippine companies and recommend reform measures for the Philippine government and the Bank. It analyzes the historical developments of the corporate sector, the legal and regulatory framework for the corporate governance, the ownership and control of publicly listed companies, and corporate performance and financing relative to corporate governance factors. The study addresses weaknesses in corporate governance by introducing reforms in the policy and regulatory framework and by actively promoting the development of both capital market and product-factor markets. The two major areas for reforms can be divided into the two traditional classes of controls of corporate governance-internal control system and external controls and discipline. Internal controls are the corporate governance systems within the company that are mandated by the Corporation Code and enforced within the company. External controls and discipline emanate from actions by customers and investors in the product and capital markets, respectively. The government, acting in the public interest, regulates companies to prevent malpractice and to promote the development of markets.